The relationships between work-life balance, job-related affective well-being, and family-friendly policies at the time of COVID-19 - Koç, Ceyda (My University, 2023)
Bu çalışmanın amacı İş Yaşam Dengesi, İşe Bağlı Duygusal Esenlik ve Aile Dostu Politikalar arasındaki ilişkilerin Covid-19 zamanında incelenmesidir. Bu kapsamda Türkiye’de özel sektörde çalışan 317 çalışandan veri toplanmıştır. Yapılan analizlerin sonucunda İş Yaşam Dengesinin İşe Bağlı Duygusal Esenliğe pozitif bir katkısı olduğu bulgulanmıştır. Aile Dostu Politikalar’ın, İş Yaşam Dengesi ve İşe Bağlı Duygusal Esenlik arasındaki ilişkiye herhangi bir düzenleyici etkisi saptanamamıştır. Ancak Aile Dostu Politikalar ve İşe Bağlı Duygusal Esenlik arasında pozitif bir ilişki bulunmuştur. Araştırmanın verileri toplanırken Covid-19 döneminde ortaya çıkmış olan yeni çalışma modelleri (karma ve uzaktan çalışma modelleri) de demografik bilgi formunda toplanmıştır. Çalışma modelleri (Ofis, karma ve uzaktan) ile İş Yaşam Dengesi ve İşe Bağlı Duygusal Esenlik arasındaki ilişki ANOVA analizi ile incelenmiştir. Bu analiz sonucunda İş Yaşam Dengesi ve İşe Bağlı Duygusal Esenlik’in ofiste çalışanlara kıyasla, uzaktan ve karma çalışanlarda daha yüksek olduğu sonucuna ulaşılmıştır. Araştırmanın sonuçları alanyazın ışığında tartışılmıştır.

The purpose of this study is to examine the relationship between Work-Life Balance, Job-Related Affective Well-Being, and Family-Friendly Policies during Covid-19 period. In this context, data were collected from 317 employees working in the private sector in Turkey. As a result of the analyses, it was found that Work-Life Balance has a positive contribution on Job-Related Affective Well-Being. No moderating effect of Family Friendly Policies on the relationship between Work-Life Balance and Job-Related Affective Well-Being was found. However, a positive relationship was found between Family Friendly Policies and Job-Related Affective Well-Being. While collecting the demographic data of the study, information on working models (hybrid and remote working) that emerged during the Covid-19 period was also collected in the demographic information form. The relationship between working models (office, hybrid and remote) and Work-Life Balance and Well-Being was analyzed with ANOVA analysis. As a result of this analysis, it was found that Work-Life Balance and Job-Related Affective Well-being were higher in remote and hybrid working employees compared to office working employees. The results of the study are discussed in light of the literature.
COVID-19 döneminde iş-yaşam dengesi, işe bağlı duygusal esenlik ve aile dostu politikalar arasındaki ilişkiler
Keywords: Aile Dostu Politikalar; COVID-19 (Disease); COVID-19 (Hastalık); Covid-19; Covid-19. Work-life Balance; Esenlik; Family-Friendly Policies; İş Yaşam Dengesi; İşe Bağlı Duygusal Esenlik; Job-Related Affective Well-Being; Psikolojik yönleri; Psychological aspects; Well-Being